Portrayal of Women’s Issues in PTV Drama Serials: An Overview - Qaiser, Saleem Abbas; Jabeen, Firasat (Bodhi: An Interdisciplinary Journal, 2010)
This article attempts to present an overview of portrayal of women's issues in Pakistan Television (PTV) drama serials. Women's issues have been concerns of PTV programs since its early days. Particularly, drama serials have been significant in this regard. However, it is a matter of study whether they are really serious on the problems of women or whether they portray women in a stereotypical images. DOI: 10.3126/bodhi.v2i1.2873 Bodhi Vol.2(1) 2008 p.211-218